CRIMINAL OFFENCE OF EXTRAMARITAL UNION WITH A MINOR DE LEGE LATA AND DE LEGE FERENDA - Miladinović Stefanović, Dušica (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
Minors enjoy a special status within the framework of criminal law, regardless of whether they are perpetrators or victims of crimes. It is fully understandable and justifiable considering the characteristics of this social category, which includes young people who are still in the process of biological, psychological and social formation, development and maturation. Although Serbian law has traditionally recognized the need for rules adapted to this social category, certain steps have been taken in recent times to ensure their more comprehensive protection. Thus, for the first time in our legal system, the 2005 Act on Juvenile Offenders and Protection of Minors in Criminal law (Juvenile Justice Act) unified specific legal solutions from the area of substantive, procedural and enforcement criminal law within the framework of an independent source of law. This tendency was pursued in the Act on Special Measures for the Prevention of Criminal Offenses against Sexual Freedom involving Minors (2013), which envisaged special records on sex offenders, introduced a ban on mitigation of punishment and parole, prescribed no statute of limitations on criminal prosecution and execution of punishment in sex offences involving minors, as well as special legal consequences of conviction. The same is the case with the earlier amendments of the Criminal Code, carried out in the process of harmonization with the Council of Europe Convention on the Protection of Children from Sexual Exploitation and Sexual Abuse, as well as with the last one from 2019, which introduced life imprisonment, precisely with the aim of ensuring adequate answer for the perpetrators of the most serious crimes against life and limb and sex crimes, in case the consequence of the crime is the death of a child, a minor, a pregnant woman, or an infirm person. The same conceptual framework was pursued by the working group created by the Ministry of Justice for drafting the legislative act on the so-called Amber Alert, a special mechanism for instituting a faster and more efficient search for missing or abducted children. However, in these efforts to strengthen the criminal-law protection of minors, it seems that one of the criminal offences against marriage and family somehow remained "under the radar": the criminal offence of extramarital union or cohabitation with a minor (Article 190 CC). There seems to be no need to specifically elaborate on and justify the thesis that life in an extramarital union can be harmful for a minor in many ways, in terms of health, education, economic situation, etc. Moreover, this micro-cohabitation community may be “a screen” disguising violence, sexual, labor or other forms of exploitation and abuse of minors. In this context, the subject matter of research in this paper is the normative framework of this criminal offence, i.e. whether the legal provisions in Article 190 of the CC and their application in the practice of domestic courts are appropriate in view of achieving the criminal-policy goals which triggered the criminalization of this offence.